REDUCING SMELTING OF CASSITERITE CONCENTRATE IN AN IONIC MELT - Hosen Ri; V. V. Gostishchev; E. H. Ri (Литьë и металлургия)
The features of coal chemical recovery cassiterite concentrate in molten salt system Na2Co3–NaNO3  (1:0,3) were studied. It is shown that cassiterite (SnO2) in the salt melt (900–950 °C) proceeds in the form metastannate (Na2SnO3) and reduced to the metal, mainly gas CO, with high speed and completeness (97%).